Strengthening Character through the Application of Pancasila Values in Science Content Thematic Learning in Elementary Schools - Eka Selvi Handayani; Wahyu Setyaningsih; Muhammad Zaibi; Sukriadi Sukriadi; Nur Agus Salim (Postgraduate, University of Mataram, 2023)
This research is a qualitative research whose background is that there are still some students who still do not reflect Pancasila behavior both during learning and outside of learning. This study aims to analyze character strengthening through the application of Pancasila values ​​in thematic learning of science content at SDN 008 Samarinda Ulu. The technique used in this triangulation is triangulation of data sources to test the validity of the data. The results of research that has been carried out by researchers in class IVB SDN 008 Samarinda Ulu is that the teacher has applied Pancasila values ​​in the thematic learning of science content so that it influences student character. Its application is by getting students to pray, say hello, greet. The teacher gives freedom to students to express opinions, respect differences, help others, consult, and be fair when learning takes place which is integrated with strengthening religious, national, independent and mutual cooperation characters. There are no difficulties in strengthening character through the application of Pancasila values ​​in thematic learning